Synthesis and evaluation of raloxifene derivatives as a selective estrogen receptor down-regulator. Issue 13 (1st July 2016) - Shoda, Takuji; Kato, Masashi; Fujisato, Takuma; Misawa, Takashi; Demizu, Yosuke; Inoue, Hideshi; Naito, Mikihiko; Kurihara, Masaaki
Graphical abstract: Abstract: Estrogen receptors (ERs) play a major role in the growth of human breast cancer cells. A selective estrogen receptor down-regulator (SERD) that acts as not only an inhibitor of ligand binding, but also induces the down-regulation of ER, would be useful for the treatment for ER-positive breast cancer. We previously reported that tamoxifen derivatives, which have a long alkyl chain, had the ability to down-regulate ERα. With the aim of expanding range of the currently available SERDs, we designed and synthesized raloxifene derivatives, which had various lengths of the long alkyl chains, and evaluated their SERD activities. All compounds were able to bind ERα, and RC10, which has a decyl group on the amine moiety of raloxifene, was shown to be the most potent compound. Our findings suggest that the ligand core was replaceable, and that the alkyl length was important for controlling SERD activity. Moreover, RC10 showed antagonistic activity and its potency was superior to that of 4, 4′-(heptane-4, 4-diyl)bis(2-methylphenol) (18 ), a competitive antagonist of ER without SERD activity. These results provide information that will be useful for the development of promising SERDs candidates.